Zinc(II) phthalocyanine-viologen dyads: synthesis, electrochemistry, spectroelectrochemistry, electrodeposition, and electrochromism - Yildiz, Burak; Ahmetali, Erem; Budak, Ozlem; Koca, Atif; Sener, M. Kasim (ROYAL SOC CHEMISTRY, 2022)
Viologen (V)-modified asymmetric zinc(II) phthalocyanines (ZnPcs) were synthesized. Redox mechanisms of ZnPcs were determined with electrochemical and in situ spectroelectrochemical measurements. While ZnPc-Br illustrated common Pc-based electron transfer reactions, ZnPc-V and ZnPc-MV gave viologen and methyl-viologen (MV)-based reduction couples in addition to the Pc-based processes. During the reduction of dicationic viologen groups, ZnPc-V and ZnPc-MV complexes were electrodeposited on the electrode surface with repetitive cyclic voltammetry. The reduction processes of the V and MV groups considerably influenced the in situ spectroelectrochemical responses of the complexes. The distinct spectral changes during the redox reactions of ZnPc-V and ZnPc-MV indicated their possible use in electrochromic applications. Thus, ZnPc-V and ZnPc-MV were electrodeposited on indium tin oxide-coated glass electrodes (ITO) and investigated as potential electrochromophores. The electrochromic responses of these complexes are completely different from those of viologens and MPcs reported in the literature. Electrochromic measurements of the complexes indicated fast and reversible color changes with reasonable optical contrasts between various colors. Also, viologen groups extended the reduction reactions and considerably influenced the color changes of the complexes. Optical changes in the cyan color and low transmittance in the visible region indicated the functionality of the complexes for the construction of private places for the absolute proprietary. Moreover, the complexes have functionality for color changes from cyan to purple and pink as the anodes for electrochromic devices.
Keywords: IN-SITU SPECTROELECTROCHEMISTRY; THIN-FILMS; METAL-FREE; SPECTROSCOPY; COLORATION; DEVICE; Chemistry